Waqf-Based Pesantren's Strategy In Developing of Human Capital and Entrepreneurship Education - Alfarid Fedro; Syamsuri; Syamsuddin Arif; Wibisono, Vina Fithriana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aims to study the management of waqf-based Pesantren's strategy namely Pondok Modern Darussalam DarussalamGontor (PMDG) in developing human capital and entrepreneurship education for educational independence, as for this research related to the management of waqf. This research using qualitative descriptive methods and data obtained through triangulation techniques. As a result, waqf-based pesantren strategies in developing educational independence through community-based education (Kiai, teachers, santri, and society) make the harmony of pesantrenlife with all its totality a medium of learning and education combined with a culture of values ​​and philosophy, leadership and strengthening of modern systems management to product people who embedded 3 intelligences; iman (in faith), ilmu (in knowledge), and amal (in deed) those are supported by the management and development of waqf as an instrument for developing human capital and entrepreneurial education. The implication of this research is to make the management of waqf in waqf-based educational institutions as an instrument to develop and improve the accountability of waqf management to stakeholders.